2013
DOI: 10.1038/nature12523
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastable silver nanoparticles

Abstract: Noble-metal nanoparticles have had a substantial impact across a diverse range of fields, including catalysis, sensing, photochemistry, optoelectronics, energy conversion and medicine. Although silver has very desirable physical properties, good relative abundance and low cost, gold nanoparticles have been widely favoured owing to their proved stability and ease of use. Unlike gold, silver is notorious for its susceptibility to oxidation (tarnishing), which has limited the development of important silver-based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

33
1,162
1
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,068 publications
(1,200 citation statements)
references
References 31 publications
33
1,162
1
4
Order By: Relevance
“…We found that the [Ag 25 31 , a stability that could not be obtained with other protecting ligands 11,32,12,25 .…”
Section: Supporting Information Placeholdermentioning
confidence: 81%
See 1 more Smart Citation
“…We found that the [Ag 25 31 , a stability that could not be obtained with other protecting ligands 11,32,12,25 .…”
Section: Supporting Information Placeholdermentioning
confidence: 81%
“…The Ag 25 was also found to exhibit luminescence in the near-infrared region ∼850 nm. Typically, silver clusters are brown to red 11,[26][27][28] and usually are associated with that color, but the color resemblance between Ag 25 cluster and that of large plasmonic Ag nanoparticles may have delayed its discovery. To naked eyes, the purified Ag 25 cluster solution appeared yellow (Figure 1, inset) similar to Au 25 prepared ( Figure S2) using the same thiol.…”
Section: Supporting Information Placeholdermentioning
confidence: 99%
“…[1][2][3] Most of the reports on such clusters are concerned with gold but a few analogues of silver and copper have also appeared in the literature. [4][5][6][7][8][9][10] Molecules such as Au25SR18, [11][12][13] Au38SR24 14 and Au144SR60 15 are some of the most stable species in this family of materials. Catalytic and biological applications of such materials are fast evolving.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10] The geometric structures of such precise metal clusters can be determined via single-crystal X-ray structural analysis. Therefore, our knowledge of the geometry of metal clusters protected by organic ligands is currently improving rapidly.…”
Section: Introductionmentioning
confidence: 99%